1990
DOI: 10.1111/j.1365-2826.1990.tb00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Progestin Receptor Induction and Sexual Behavior by Estradiol Treatment in Male and Female Rats

Abstract: Sex differences in the induction of cytosolic progestin receptors (CPR) by estrogen priming were correlated with the sex differences in behavioral responses. We evaluated the temporal relationship between CPR in several brain regions and pituitary and the timecourse of 17P-estradiol (E,) activation of female sexual behavior in gonadectomized male and female rats implanted with sribcutaneous E, Silastic capsules for 6 h, 24 h and 48 h. Both CPR levels and mating behavior increase monotonically with the time 0; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…The fact that these sex differences are evident after the critical period of sex ual differentiation but before puberty strongly suggests that they are the product of the developmental actions of testosterone in males, rendering them less sensitive to estradiol. This has pre viously been observed for progestin receptor induction in the VMN [45][46][47] and shown to depend on the postnatal organiz ing effects of testosterone [48] in determining the neurotrophic response of the VMN neurons to estradiol.…”
Section: Functional Implications and Possible Mechanismsmentioning
confidence: 69%
“…The fact that these sex differences are evident after the critical period of sex ual differentiation but before puberty strongly suggests that they are the product of the developmental actions of testosterone in males, rendering them less sensitive to estradiol. This has pre viously been observed for progestin receptor induction in the VMN [45][46][47] and shown to depend on the postnatal organiz ing effects of testosterone [48] in determining the neurotrophic response of the VMN neurons to estradiol.…”
Section: Functional Implications and Possible Mechanismsmentioning
confidence: 69%
“…The absence of dif ferences in the numbers of PR-IR cells in the Ar is in agreement with the measurements of PR made by Thorn ton et al [24], However, these authors have not deter mined whether there is any sex difference in the VL. On the other hand, in rats treated with estradiol benzoate, several studies have shown marked sex differences in the PR levels and the numbers of cells expressing PR mRNA in the ventrolateral aspect of the ventromedial nucleus and the Ar [25,26]. The discrepancies may arise from methodological differences or from differences in ana tomical definition of the regions studied.…”
Section: Discussionmentioning
confidence: 99%
“…Other sexually dimorphic membrane actions of steroids like the modula tion of dopamine release by E in the striatum, have been associated with sexually dimorphic sensorimotor func tions [34], However, a reduced effectiveness of E in induc ing intracellular receptors for P also contributes to the be havioral insensitivity of male rats to P [35,36] and the activation of protein synthesis by P bound to estrogen-in duced receptors is important for the facilitation of lor dosis behavior [37,38]. Thus, sexually dimorphic geno mic and membrane actions of steroid hormones may both contribute to the sexual dimorphism that affects repro ductive behavior.…”
Section: Discussionmentioning
confidence: 99%